Mechanical properties of sugar palm lignocellulosic fibre reinforced polymer composites: a review - M. R., M. Asyraf; M., Rafidah; Ebadi, S.; A., Azrina; M. R., Razman (Springer, 2022)
The significant reduction in petroleum resources and the growth of global environmental awareness on the use of conventional plastics are the motivating factors to accept natural fibres as green materials. Lignocellulosic fibre-reinforced polymer biocomposites have attracted considerable attention from engineers and researchers because of their sustainable nature and wide availability. Sugar palm is an emerging crop grown in Malaysia and Indonesia and is regarded as a significant candidate lignocellulosic fibre in biocomposites. Sugar palm fibres are mainly made up of cellulose, which leads to outstanding mechanical properties. From a literature review, no comprehensive review paper has been published on the mechanical behaviour of sugar palm lignocellulosic fibre biocomposites to provide a good source of literature for doing further research on this topic to consider them construction and building materials. The present review concentrates on recent work on the properties of sugar palm lignocellulosic fibres, starches, and nanofillers and their fabrication as biocomposites.